2018
DOI: 10.1002/er.4127
|View full text |Cite
|
Sign up to set email alerts
|

A semiempirical dynamic model of reversible open circuit voltage drop in a PEM fuel cell

Abstract: Summary Fuel cell voltage modeling is important for fundamental research. The main focus of previous studies has been the working voltage segment, whereas the accuracy of the open circuit voltage (OCV), especially the dynamic OCV change process, has been ignored. A semiempirical model including the OCV and an electrochemical model has been proposed in this study to clarify the reversible voltage drop process. A mixed cathode potential drop that is assumed as corresponding to a piecewise function relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The authors found that both factors were significant, with the oxide formation accounting for a potential drop three to four times that of the crossover. Hu et al 11 developed a semi-empirical model to account for the drop in OCV observed upon start up in a fuel cell bus. The model assumed that oxide formation and hydrogen crossover contribute to the OCV with the dynamic behavior being caused by changes in the electrochemical surface area (ECSA) from further oxide formation and platinum dissolution.…”
mentioning
confidence: 99%
“…The authors found that both factors were significant, with the oxide formation accounting for a potential drop three to four times that of the crossover. Hu et al 11 developed a semi-empirical model to account for the drop in OCV observed upon start up in a fuel cell bus. The model assumed that oxide formation and hydrogen crossover contribute to the OCV with the dynamic behavior being caused by changes in the electrochemical surface area (ECSA) from further oxide formation and platinum dissolution.…”
mentioning
confidence: 99%
“…The difference between the theoretical open circuit voltage (OCV), E, calculated with Equation (2) and experimental OCV, U OCV exp , is considered to be caused by two different drops in potential [53][54][55]. A first voltage drop, ∆U OCV Pt−O 2 , is associated with the Pt-O 2 reaction mechanism at the cathode electrode in an oxygen saturated acidic solution.…”
Section: Results and Discussion Polarization Profiles And Overall Power Performancementioning
confidence: 99%
“…A first voltage drop, ∆U OCV Pt−O 2 , is associated with the Pt-O 2 reaction mechanism at the cathode electrode in an oxygen saturated acidic solution. When a PEM fuel cell starts from 0 V to OCV, an increase from 0% to 70% of the platinum surface fraction covered by PtO will be registered [54] /g) in such a way that an ECSA increasing will produce a decreasing of the two above mentioned voltage drops. The cyclic voltammetry investigations performed on the LIG-based MEA and CB-based MEA with results reported in a previous work [34] revealed an 18% and 25% increasing of the ECSA values for Test 1 and Test 3 operating conditions of the fuel cell containing LIG MEA.…”
Section: Results and Discussion Polarization Profiles And Overall Power Performancementioning
confidence: 99%
“…1 In particular, emission reduction from the automotive industry attracts great attention from governments and societies. Among all the possible solutions, proton exchange membrane fuel cells (PEMFC) are regarded as a promising power source for commercial vehicles, [2][3][4] with advantages of high efficiency, zero-emission, low noise, short start time at low temperatures, and long driving distance. [5][6][7][8] Recently, with a rapid reduction of cost and improvement of performance, fuel cell technology again becomes a hotspot in the research of new energy vehicles.…”
Section: Introductionmentioning
confidence: 99%